PENGEMBANGAN KOMODITAS SAGU DI KABUPATEN KEPULAUAN MERANTI - Sirojul Abidin; Zaili Rusli SD (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
The development of sago is an opportunity to improve the economy of the people of the Meranti Islands Regency. The development of Sago Commodity in the Meranti Islands Regency is aimed at the greatest possible welfare of the people of the Meranti Islands Regency through the sago development program with the establishment of the Meranti Islands Regency as the center of excellence for the national sago commodity. The purpose of this study was to determine the supporting and inhibiting factors for the development of sago in the Meranti Islands Regency. This study uses purposive sampling technique and qualitative research uses a descriptive approach and uses data collection techniques by means of observation, interviews and documentation to be analyzed further. The results of this study indicate that: first, the development of Sago Commodity in the Meranti Islands Regency is running well, marked by an increase in the amount of sago production per year. Second, the supporting factor for the development of this area is the geographic condition of the Meranti Islands Regency with 60% of the area consisting of peat soils and modern production equipment. Keywords: program, superior commodity of sago, regional income